Pseudomonas spp. can help plants face climate change - Zboralski, Antoine; Filion, Martin (Frontiers in Microbiology, 2023)
Climate change is increasingly affecting agriculture through droughts, high salinity in soils, heatwaves, and floodings, which put intense pressure on crops. This results in yield losses, leading to food insecurity in the most affected regions. Multiple plant-beneficial bacteria belonging to the genus Pseudomonas have been shown to improve plant tolerance to these stresses. Various mechanisms are involved, including alteration of the plant ethylene levels, direct phytohormone production, emission of volatile organic compounds, reinforcement of the root apoplast barriers, and exopolysaccharide biosynthesis. In this review, we summarize the effects of climate change-induced stresses on plants and detail the mechanisms used by plant-beneficial Pseudomonas strains to alleviate them. Recommendations are made to promote targeted research on the stress-alleviating potential of these bacteria.